Combined Scraping, Coagulation, and Subconjunctival Bevacizumab in Descemet Stripping Automated Endothelial Keratoplasty for Bullous Keratopathy. Issue 3 (May 2013) - Chiang, Chun-Chi; Lin, Jane-Ming; Tsai, Yi-Yu
Purpose: This study evaluated the clinical outcomes of a combined method of scraping corneal epithelium, coagulating vessels, and subconjunctival bevacizumab in Descemet stripping automated endothelial keratoplasty (DSAEK) for bullous keratopathy with corneal neovascularization (NV). Methods: The study included patients with bullous keratopathy undergoing DSAEK. Indications for DSAEK were advanced pseudophakic bullous keratopathy with superficial and deep corneal vascularization and failed corneal grafts. Patients were treated by scraping the corneal epithelium and lightly coagulating the corneal superficial stromal NV and the feeding vessels in the sclera, with a subconjunctival bevacizumab injection at the end of surgery. Subconjunctival and perilimbal bevacizumab dose of 2.5 mg/0.1 mL/affected quadrant was injected at the site of NV in each patient at the end of surgery. One or 2 injections were applied. At each visit, a full eye examination with photographic documentation was performed. Mean follow-up period was 32 (24 –36 ) months. Results: Eight eyes of 8 patients with high-risk corneal transplantation and corneal NV were included in this noncomparative interventional case series. The original corneal NV disappeared in all patients immediately after surgery. No patient in the series had recurrent corneal NV or rejection during at least 24 months of follow-up. Conclusions: The combination of scraping, coagulating, and bevacizumab injection in DSAEK is an effective method to treat corneal NV in corneal transplantation for bullous keratopathy.